Penyuluhan Dan Pelatihan Tentang Manfaat Latihan Fisik Aerobik Dan Pemberian Multivitamin - Donna Adriani; Patwa Amani; Mustika Anggiane Putri; Irmiya Rachmiyani; Yudhisman Imran (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The World Health Organization has declared that March 11, 2020 as a COVID-19 pandemic. One of the risk factors for someone infected with COVID-19 is a decrease in body resistance. Aerobic exercise is effective in increasing immunity by increasing antioxidants in the body and lowering oxidants. An increased immune system can prevent the spread of COVID-19. Aerobic exercise can also improve  cognitive function of people who do more activities at home. Therefore, knowledge, attitudes, and behavior towards aerobic exercise are very important and useful as an effort to prevent the spread of COVID-19 and improve cognitive function. The purpose of this activity is that participants can do aerobic exercise independently and regularly so as to increase endurance and cognitive function. The method of this activity is filling out questionnaires by 30 participants before and after seminar through the zoom meeting application. The study showed that there were 45.13 ± 17.84 years old, lack of knowledge, good attitude, and good behavior. The results of the research after seminar were 45.13 ± 17.84 years old, good knowledge, good attitude, and good behavior. Based on the results of the research above, it can be said that seminar can increase public knowledge.